Modal analysis of 2.5 inch seagate hard disk drive using laser doppler vibrometer - Tay, Meng Heng. (2010)
Hard disk drives (HDD) have evolved over the century from being just a part of the desktop PC to being part of almost every electronic gadget that we can find today. From hand held gaming devices to laptops, mobile phones as well as cameras, almost every electronic device with memory storage function will require a hard disk drive. Increase need for portability and mobility of these electronic gadgets raised concerns on the durability of hard disk drives when subjected to vibrations. These led to an increase interest in the dynamic and mechanical properties of the hard disk drives when subjected to shock.